FEATURES CITOLOGICAL CHANGES IN THE TESTIS IN A BLOCKADE OF BLOOD FLOW ARTERY OF THE VAS DEFERENS - Лісова, Т.А. (World of Medicine and Biology, 2015)
Vasectomy for a long time is one of the important methods of contraception [1, 3, 7, 8]. However, the literature of clinical andrology when describing vasectomy technicue does not specify whether stored artery blood flow while the ejaculatory ducts, which in the second lumen artery that supplies the testicle. Therefore, the study of the effect of blockade of the artery on spermatogenesis is an important issue since if necessary to restore the passability of the ejaculatory ducts at remarriage divorce raises the question of its reproductive performance [4, 5, 6].The aim was to access the nature of cytological changes in the testis under conditions of blockade artery blood flow ejaculatory ducts.Material and methods. Experiments were conducted on 33 laboratory rats - males weighing 150-180 grams, divided into 4 groups with overlapping artery ligation ejaculatory ducts 1, 7 and 30 days, followed by a study of histological preparations diameter convoluted seminiferous tubules, the degree of damage , the number of cells spermatogenic epithelium 7 stage of the cycle, the volume of interstitial nuclei endocrinocytes and electron microscope study of testicular structures with an electron microscope TEM-125 K.Results and discussion. We found cytological changes in the structures of the testis, the extent of which depends on the duration of the experiment. At the 7th day of the experiment 15% of seminiferous tubules present serious degree of cell damage with a significant (p
Keywords: blockade of the ejaculatory ducts; testis; spermatogenesis